EXAMPLES OF NATURE IN JAPANESE GRAPHICS XVII – XX CENTURIES AND THEIR DISPLAYING IN ECO-POSTER - Шауліс, К. К. (Art and Design, 2019)
The aim of the work is to explore the origin and development of natural images in the art of Japan and to study their reflection in the ecological poster. The method of classification and systematic, as well as comparative-historical methods was used to identify the ecological trend in art; method of figurative and stylistic analysis. The stages of the development of Japanese art are considered in the article and the main tendencies of the development of the ecological direction in art are revealed. Based on the works of leading artists, the core images of nature in painting and graphic art of Japan are analyzed. It has been proved that the images of nature, reflected by the masters in their graphic and pictorial works of the seventeenth and twentieth centuries, have been reflected in the Japanese environmental posters. It is substantiated that every new turn of the development of the Japanese landscape genre, the images of nature overcome significant evolution and are revealed in a new way, moving from the specification and description to the reflection of the deep questions of humanity. It is argued that the ctive display of the images of nature in the engraving begins at its final stage, when the fuke-ha landscape (landscapes), kate-ha (flowers and birds) develop in the development of the genre, in which the love of the Japanese to the surrounding world is fairly vividly demonstrated. It has been demonstrated that the most diverse images of nature are revealed with the emergence of the art of the poster. As an independent artistic unit, the poster is revealed rather late, but quite sparingly gains exceptional popularity. Due to its cleverness and a large range of artistic techniques, it has become one of the most prominent artistic expressions and broadcasts of information, and has become very popular in the artistic sphere of Japan and the world.